1996
DOI: 10.1063/1.116521
|View full text |Cite
|
Sign up to set email alerts
|

All-optical synchronization of self-pulsating laser diodes

Abstract: We examine the behavior of self-pulsating laser diodes when injected with periodic optical signals. We experimentally and theoretically investigate the phase difference between the injected optical signal and the synchronized self-pulsating laser diode emission. We explore the phase difference dependence on detuning between the laser free-running self-pulsation frequency and the applied signal frequency, and on the injected signal power. The determined sensitive dependence of the phase difference on these fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…It has previously been shown that there exists a power dependence of the phase difference between the injected optical signal and the laser output in a synchronized C D laser in the case of 1:l synchronization [19]. In this paper we find that, for frequency division, the sensitivity to the input power is even greater.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…It has previously been shown that there exists a power dependence of the phase difference between the injected optical signal and the laser output in a synchronized C D laser in the case of 1:l synchronization [19]. In this paper we find that, for frequency division, the sensitivity to the input power is even greater.…”
Section: Discussionmentioning
confidence: 64%
“…Full details of the experimental techniques have been given in [19]. A C D laser (slave laser) was synchronized to the optical output from an electrically synchronized C D laser (master laser) [19].…”
Section: Experimental Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…We have previously used this kind of calculation to successfully predict the behavior of the optical synchronization of a CD self-pulsating laser diode [5].…”
Section: Theorymentioning
confidence: 99%
“…The non-linear response of self-pulsating laser diodes to externally injected optical signals has been used to investigate their synchronization properties [19]. In order to study these features far from the equilibrium, we shall consider a driven diode laser model with two rate equations for the photon and carrier densities, denoted by SðsÞ and N ðsÞ, respectively, and written as [5] …”
Section: Diode Laser Modelmentioning
confidence: 99%